Taxonomic assessment of genetically-delineated species of radicine snails (Mollusca, Gastropoda, Lymnaeidae) - Maxim V. Vinarski; Olga V. Aksenova; Ivan N. Bolotov (Zoosystematics and Evolution, 2020)
The article represents an overview of 29 biological species of the radicine snails (genera Ampullaceana Servain, 1882, Bullastra Bergh, 1901, Racesina Vinarski & Bolotov, 2018, Kamtschaticana Kruglov & Starobogatov, 1984, Myxas G.B. Sowerby I, 1822, Orientogalba Kruglov & Starobogatov, 1985; Peregriana Servain, 1882, Radix Montfort, 1810, and Tibetoradix Bolotov, Vinarski & Aksenova, 2018) recovered during our previous molecular taxonomic study (Aksenova et al. 2018a; Scientific Reports, 8: 11199). For each species, the following information is provided: scientific name, a (non-exhaustive) list of synonyms, type locality, type materials, shell and copulative apparatus morphology, distribution, and nomenclatural and taxonomic remarks. The colour images of shell(s) of each species are also given as well as illustrations of the copulatory apparatuses. We revealed a great conchological variation in the radicines, both intra- and interspecific, alongside with striking uniformity in the structure of their copulatory apparatuses. The latter was once thought to be a reliable tool for species delineation and identification in this snail group. The total of 29 species characterised here represents, probably, only a subset of the global taxonomic richness of the radicine snails, which approaches 50 species.